Simplified seismic response of earth embankments - Low, Abigail Xiu Jun. (2012)
This study aims to validate the method proposed by Makdisi and Seed (1979), which provides a simplified procedure for determining the natural period and maximum crest acceleration of homogeneous earth embankments by hand calculation. A comparison was made with the results obtained using PLAXIS finite element analysis. The variation of maximum crest acceleration with increasing model geometry width was also studied.